Spectator‐filter‐spreader‐stifler information propagation model with wake‐up mechanism in social networks. (27th August 2020) - Liu, Shuqi; Sun, Chengai; Qiu, Liqing; Wei, Moji
Summary: Nowadays, social network platforms play a significant role in daily life, allowing people to hear what is going on around the world without leaving home. The research on the internal transformation of information propagation is critical, which can help restrain the propagation of fake information or rumors and promote the widespread dissemination of effective information. To better understand the transition of states in information propagation, this article considers a new filter state that does not transmit information temporarily and establishes a spectator‐filter‐spreader‐stifler (SFIR) model. Mainly, to explore the dynamics of information propagation, the article introduces two different wake‐up mechanisms including the spontaneous awakening of the filter and the infection of the leader spreaders to the passive stifler, which relies on the proportion of current spreaders as well as the doubt degree on information. Afterward, based on the average field equations built, the nonpropagation equilibrium point E 0 and propagation equilibrium point E 1 are obtained by theoretical analysis. Moreover, the simulation results reveal that spontaneous wake‐up mechanism accelerates the information propagation while leader spreaders infection increases the scope of information propagation, which can provide theoretical support for controlling information propagation more effectively.